The importance of professional skepticism in detecting money laundering: investigating officers' perspective / Sharifah Nazatul Faiza Syed Mustapha Nazri ... [et al.] - Syed Mustapha Nazri, Sharifah Nazatul Faiza; Che Jailani, Siti Hajar; Zolkaflil, Salwa; Ismail, Noor Haslina; Syed Yusuf, Sharifah Norzehan (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study aims to examine the characteristics of professional skepticism that influence money laundering detection among the investigating officers of law enforcement agencies in Malaysia. 200 questionnaires were collected and analyzed via Pearson correlation and multiple linear regression to examine the relationship between the six characteristics of Hurtt's professional skepticism (questioning mind, suspension of judgment, searching for knowledge, interpersonal understanding, self-determination, and self-confidence) and the detection of money laundering. The findings revealed that questioning mind, suspension of judgment, and self-confidence possessed stronger linear relationships and significantly influenced the detection of money laundering. Since previous studies mostly focused on professional accountants, this study contributes to the body of knowledge by looking into the importance of professional skepticism among the investigating officers working in law enforcement agencies. Hence, future studies may conduct similar studies in other countries to understand the professional skepticism characteristics among the investigating officers. This study recommends the management team of the law enforcement agencies improve training module by including enhanced professional skepticism characteristics, which will eventually improve the officers' evidence-gathering process in the future.